190 Placebo – to use or not to use? Survey on the use of placebo treatments. Issue 6 (27th May 2022) - Huys, Anne-Catherine ML; Franklin, Hannah D; Bhatia, Kailash P; Stone, Jon; Edwards, Mark J
Abstract : Patients´ and healthcare professionals´ attitudes to deceptive and open-label placebo treatments in clinical practice were evaluated by means of an anonymous survey. The overall attitude to deceptive placebo treatments was favourable amongst the 310 neurological patients and 100 medical patients/healthy participants taking part in the survey. The 90 healthcare pro- fessionals and 140 patients with a functional neurological disorder were more conservative, with equal numbers being in favour and against. An even more crucial factor is the considerable percentage being strongly opposed to deceptive placebo – 16% of neurological patients and 30% of patients with a functional neurological disorder. The majority of healthcare professionals had never used deceptive placebo, with an even smaller pro- portion ever having used open-label placebo. There was marked scepticism with regards to open-label placebo in all groups, with the general underlying belief that open-label placebo is fairly ineffective The prohibition of deceptive placebo use in the UK seems to be in line with general concerns and oppo- sition to placebo. Future studies will show if the negative attitude to open-label placebo is justified or if this ethically viable option deserves more consideration. The survey is ongoing (to take part, visit https://is.gd/hcp_placebosurvey). The final numbers and conclu- sions may thus change. anne-catherine.huys.15@ucl.ac.uk